Further evidence that paroxysmal nocturnal haemoglobinuria is a disorder of defective cell membrane lipid rafts. Issue 9 (29th May 2015) - Ratajczak, Mariusz Z.; Borkowska, Sylwia; Mierzejewska, Kasia; Kucia, Magda; Mendek‐Czajkowska, Ewa; Suszynska, Malwina; Sharma, Vivek A.; Deptala, Andrzej; Song, Wechao; Platzbecker, Uwe; Larratt, Loree; Janowska‐Wieczorek, Anna; et al.
Abstract: The glycolipid glycosylphosphatidylinositol anchor (GPI‐A) plays an important role in lipid raft formation, which is required for proper expression on the cell surface of two inhibitors of the complement cascade, CD55 and CD59. The absence of these markers from the surface of blood cells, including erythrocytes, makes the cells susceptible to complement lysis, as seen in patients suffering from paroxysmal nocturnal haemoglobinuria (PNH). However, the explanation for why PNH‐affected hematopoietic stem/progenitor cells (HSPCs) expand over time in BM is still unclear. Here, we propose an explanation for this phenomenon and provide evidence that a defect in lipid raft formation in HSPCs leads to defective CXCR4‐ and VLA‐4‐mediated retention of these cells in BM. In support of this possibility, BM‐isolated CD34 + cells from PNH patients show a defect in the incorporation of CXCR4 and VLA‐4 into membrane lipid rafts, respond weakly to SDF‐1 stimulation, and show defective adhesion to fibronectin. Similar data were obtained with the GPI‐A − Jurkat cell line. Moreover, we also report that chimeric mice transplanted with CD55 −/−  CD59 −/− BM cells but with proper GPI‐A expression do not expand over time in transplanted hosts. On the basis of these findings, we propose that a defect in lipid raft formation in PNH‐mutated HSPCs makes these cells more mobile, so that they expand and out‐compete normal HSPCs from their BM niches over time.